An Effective Absenteeism Policy: How Employers Use it to Improve Employees’ Attendance Behavior, Working Life? - Aldoghan, Mohammed; Elrayah, Musaddag (The Arab Journal of Administration, 2021)
The traditional viewpoint always looks to employees as a source of the problem. Examining the relationship between an effective absenteeism policy and employees’ attendance behavior as well as their wellbeing at work will change this viewpoint. 219 employees from the petrochemical sector in the Eastern Area targeted for this study. A sample of 139 employees selected randomly for the purpose of this study. 22 questions are formulated to study the main indicators of the relationships between the variables of this study. A self- administered questionnaire used a five-point Likert structured sent through emails to 139 respondents who represent the selected sample of employees from the eastern area industrial sector. Data collected was analyzed to provide some descriptive and correlations results. Study findings have shown a positive correlation between the variables of this study. The findings show that an effective absenteeism policy might help to decrease the work-related accidents, decrease the work-related illness, improving the overall attendance satisfaction and employees’ wellbeing.